From the Editors: Conducting high impact international business research: The role of theory - Bello, Daniel C; Kostova, Tatiana (Journal of International Business Studies, 2012)
This editorial identifies a number of potential theory-related weaknesses in manuscripts, some more general in nature, others specific to international business (IB) research. It provides a brief critique and suggestions on how to overcome common problems in motivating research, framing contributions, reviewing literature, benefiting from the review process, and other issues of conceptual development. It also addresses questions particularly critical to IB research including multidisciplinarity, utilizing international context and enhancing theoretical impact. We conclude with specific guidelines on how to emphasize theory, thereby enhancing contribution and impact, in crafting and revising submissions to JIBS.